A constitutional language name, lost in translation and its impact on the identity of the first language speakers. Issue 2 (3rd July 2019) - Rakgogo, Tebogo Jacob; van Huyssteen, Linda
Abstract : The primary aim of the study is to explore the Sepedi language name that got lost during the translation of the English version of the Final Constitution of the Republic of South Africa into the other ten official languages of South Africa and to determine how the identity of the first language (L1) speakers of the language under scrutiny has been affected by the use of both Sepedi and Sesotho sa Leboa as two designations for one official language. One hundred respondents from two South African universities were sampled to take part in the study since they were learning or lecturing the language under investigation as an applied/first language module. A quota sampling was used as well as a Likert scale-type of questionnaire to gather data from the respondents. From a purely linguistic and political point of view, the study indicated how the confusion of Sepedi and Sesotho sa Leboa as official languages denoting one and the same language may be resolved, only if interested parties could jettison their entrenched social and political interests, and undertake a sociolinguistic survey like this one, yet more on a substantial project level.